2012
DOI: 10.1177/0143624412441615
|View full text |Cite
|
Sign up to set email alerts
|

Automated optimal design methodology of elevator systems using rules and graphical methods (the HARint plane)

Abstract: The design of an elevator system heavily relies on the calculation of the round-trip time under up-peak (incoming) traffic conditions. The round-trip time can either be calculated analytically or by the use of Monte Carlo simulation. However, the calculation of the round-trip time is only part of the design methodology. This paper does not discuss the round-trip time calculation methodology as this has been addressed in detail elsewhere. This paper presents a step-by-step automated design methodology which giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…Table 2 summarizes the resulting designs for all the five buildings. The design methodology followed was based on the procedure detailed in the following references (Chartered Institute of Building Services Engineers, 37 Barney and Al-Sharif, 38 Al-Sharif et al, 39 Roschier and Kaakinen, 40 Peters, 41 Al-Sharif and Abu-Alqumsan, 42 Al-Sharif et al, 43 Al-Sharif et al, 35 Al-Sharif and Abu Alqumsan, 44 and Al-Sharif 45 ).…”
Section: Design Of Buildingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 summarizes the resulting designs for all the five buildings. The design methodology followed was based on the procedure detailed in the following references (Chartered Institute of Building Services Engineers, 37 Barney and Al-Sharif, 38 Al-Sharif et al, 39 Roschier and Kaakinen, 40 Peters, 41 Al-Sharif and Abu-Alqumsan, 42 Al-Sharif et al, 43 Al-Sharif et al, 35 Al-Sharif and Abu Alqumsan, 44 and Al-Sharif 45 ).…”
Section: Design Of Buildingsmentioning
confidence: 99%
“…The design for each of the two sectors (upper and lower) can now be carried out in accordance with the methodology presented in Al-Sharif et al 43 The results are shown in Table 4.…”
Section: Case I Design (Constant Arrival Rate and Reduced Car Loading)mentioning
confidence: 99%
“…It is based on incoming traffic only from a single entrance. The software consists of two parts: a calculation part that carries out the design of the elevator traffic system using the HARint plane methodology 36,37 ; and a simulation part that receives the parameters of the elevator traffic system design from the calculation part and carries out the simulation for a specified period of workspace ( WS ). The simulation produces graphical outputs as well as spreadsheet data for the following parameters:…”
Section: Description Of the Softwarementioning
confidence: 99%
“…According to the rules about speed governor in national standard GB 7588--2003 section 9.9, governor which controls car safety gear, would be electrically triggered once the speed of car reaches 115% of its rated speed [6][7][8][9]. According to national standard GB 7588--2003 section 9.9.1(c), for the progressive type safety gear of which the rated speed is less than or equal to 1m/s, its action speed is 1.5m/s; and according to national standard GB 7588--2003 section 9.9.1(d), for the progressive type safety gear of which the rated speed is more than 1m/s, its action speed is:…”
Section: Performance Analysis For the Electronic Governor On The Highmentioning
confidence: 99%